Desain Dan Analisis Kinerja Pemotong Rumput Portable Dan Rechargeable - Aditya, Rahardian Krisna; , Dr. Agus Ulinuha, ST. MT, Ph.D (2016)
The utilization of fossil oil is still dominant in the use of day-to-day. The needs of energy will still increase that will cause an increasing of the needs of fossil oil from time to time. Based on the topic, the purpose of this research is grass cutter which are environmentally friendly and practical in daily use. Design of development grass cutter is using electric resources from storage battery is connected with DC motor for running the electric mower. Large capacity of battery storage is be used in designing grass cutter is 12 V 6Ah. DC Motor speed control settings using PWM method and charging the accumulator using the transformer 3 A. Observation done by taking data related with rated voltage and current at battery storage, speed of the grass cutter is when using the load nor is not using the load and duration of working tools. The result of experiment without load is showing that 1,03 A on voltage 12 V battery storage. The maximum speed of motor without load is 2460 rpm. While electrical flow consumption with load is 1,15 A and 2,98 A with maximum speed of 2441 rpm and 2320 rpm. The equipment were used for this measurement is: Multimeter, is used to measure was current and voltage of DC motor. Tachometer, was used to measure the speed of DC motor. Stopwatch, was used to measure the length of time the mower works. The result of experiment also shows that grass mower can be used for 300 minute and 120 minute with full charged of battery storage